The Urgency of Women’s Legislative Representation: Education and Political Participation - Humiati Humiati; Kristina Sulatri (Universitas Islam negeri Mahmud Yunus Batusangkar, 2025)
Women’s representation in legislative bodies is a constitutional mandate and a key indicator of democratic quality and gender equality. Although Indonesia has established a minimum 30% quota through Law No. 7 of 2017 on General Elections, representation reached only 21% in the 2019–2024 period. This study examines the constitutional and gender equality foundations of women’s representation, identifies barriers to achieving the quota, and analyzes the role of education in enhancing women’s political participation. Using a qualitative normative-juridical approach and literature review, the research analyzes statutory regulations, scholarly works, and statistical data. Findings show that women’s representation is grounded in Articles 27 and 28 of the 1945 Constitution and reinforced by international commitments such as CEDAW. Major obstacles include entrenched patriarchal culture, double burden, limited access to education, gender-biased political party systems, weak law enforcement, economic constraints, political violence, and an electoral system that does not fully support affirmative action. Education functions as a transformative instrument through formal education, practical political training, and political literacy development. Policy recommendations include integrating gender equality into curricula, strengthening structured political training, enhancing digital literacy, and implementing regulatory reforms such as the zipper system and legal protection against gender-based political violence.